The effect of moisture and temperature on the ultrastructure and viability of seeds of Hevea Brasiliensis - Chin, H. F.; Aziz, Maheran; Ang, B. B.; Hamzah, Samsidar (International Seed Testing Association, 1981)
Freshly harvested Hevea seeds of 36 % moisture content were dried by different methods and some kept moist for a period of 96 hours. Irrespective of the method of drying, dehydration of seeds resulted in loss of viability. The critical moisture content level was around-~5-20%, below this seeds were killed. Over a period of 96 hours seeds which retained their original moisture content showed little or no loss in viability at mean temperatures of22"C and 28 "C, but those stored either at -SoC or45°Clost viability completely. Exposure of seeds to -5 cC and 45°C for even two hours and 24 hours respectively produced a number of abnormal seedlings on germination. Thus seeds are killed by dehydration, high temperature or freezing. The ultrastruc- ture of cells of viable seeds under moist conditions showed no abnormality. In contrast in seeds killed by 32 hours of sun drying, there was damage to the cell wall and in the cell membranes; the nuclear membrane was not well defined and in some cells the nucleolus was indistinct. Possible causes of loss of viability in typical recalcitrant seeds are discussed.